1995
DOI: 10.1021/jf00057a033
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fate of [14C]Acrolein under Aerobic and Anaerobic Aquatic Conditions

Abstract: The metabolic fate of the irrigation canal herbicide MAGNACIDE H [active ingredient, acrolein (2-propenal)] was studied using natural sediment and water under aerobic and anaerobic aquatic controlled laboratory conditions. Test systems were treated at the recommended application rate of 15 mg/L. Water, sediment, and volatile trap analyses were performed to determine the chemical degradation pattern of acrolein. The half-life of acrolein was approximately 1 day, resulting in the production of several metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The downstream concentration of the chemical was measured as a function of time at several sites along the first 5 km from the application point. The measurement was made with a colorimeter (Hach DR100) by conversion of acrolein to 2,4‐dinitrophenylhydrazine (DNPH) (Smith et al. , 1995).…”
Section: Methodsmentioning
confidence: 99%
“…The downstream concentration of the chemical was measured as a function of time at several sites along the first 5 km from the application point. The measurement was made with a colorimeter (Hach DR100) by conversion of acrolein to 2,4‐dinitrophenylhydrazine (DNPH) (Smith et al. , 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Field experiments have demonstrated that the presence of acrolein in agricultural canals is transient (Nordone et al 1996a;Nordone et al 1996b) with a half-life ranging from 2 to 10 hr. The degradation of acrolein in water is due largely to its rapid hydrolysis to 3-hydroxy-propanal and biotransformation to acrylic acid and allyl alcohol (Smith et al 1995). Thus, under normal circumstances, irrigated crops would be exposed to minimal levels of acrolein and are more likely to come in contact with acrolein metabolizes that are metabolized to carbon dioxide in both microbial and mammalian systems (Smith et al 1995;Ghanayem et al 1987).…”
Section: Resultsmentioning
confidence: 99%
“…At the application rate of 15 ppm acrolein into irrigation canals, the primary microbial degradation product was 3-hydroxypropanal. Other ephemeral products such as acrlylic acid, allyl alcohol, propionic acid, propanol, and 3-hydroxipropionic acid were also identified (Smith et al, 1995). The high water solubility of acrolein and low estimated Koc suggests that acrolein does not significantly adsorb to suspended solids and sediment (HSDB, 2010;U.S.EPA, 2007).…”
Section: Fate Of Acrolein After Direct Application Into Irrigation Camentioning
confidence: 99%